Surface modification of bacterial cellulose aerogels' web-like skeleton for oil/water separation - Sai, Huazheng; Fu, Rui; Xing, Li; Xiang, Junhui; Li, Zhenyou; Li, Fei; Zhang, Ting (ACS applied materials & interfaces, 2015)
The cellulose nanofibers of bacterial cellulose aerogel (BCA) are modified only on their surfaces using a trimethylsilylation reaction with trimethyichlorosilane in liquid phase followed by freeze-drying. The obtained hydrophobic bacterial cellulose aerogels (HBCAs) exhibit low density (≤6.77 mg/cm(3)), high surface area (≥169.1 m(2)/g), and high porosity (≈ 99.6%), which are nearly the same as those of BCA owing to the low degrees of substitution (≤0.132). Because the surface energy of cellulose nanofibers decreased and the three-dimensional web-like microstructure, which was comprised of ultrathin (20-80 nm) cellulose nanofibers, is maintained during the trimethylsilylation process, the HBCAs have hydrophobic and oleophilic properties (water/air contact angle as high as 146.5°) that endow them with excellent selectivity for oil adsorption from water. The HBCAs are able to collect a wide range of organic solvents and oils with absorption capacities up to 185 g/g, which depends on the density of the liquids. Hence, the HBCAs are wonderful candidates for oil absorbents to clean oil spills in the marine environment. This work provides a different way to multifunctionalize cellulose aerogel blocks in addition to chemical vapor deposition method.